Dealing with the Size Effect in Insulating Liquids. A Volume Effect, an Area Effect or even a Particle Effect? A Concise Review - Danikas, M.; Sarathi, R.; Vardakis, G. E.; Morsalin, S. (Engineering, Technology & Applied Science Research, 2020)
Insulating liquids play an important role as insulating media in various high voltage applications and infrastructure installations. The dielectric strength of an insulating liquid depends on the experimental conditions (in case of laboratory testing) and/or the service conditions (in case of apparatuses in service). One of the main factors affecting the dielectric strength of insulating liquids is the so-called size effect, i.e. the effect of the size of the electrodes, of the size of the liquid volume under stress and of the gap spacing between the electrodes. All the aforementioned parameters are investigated in the context of the present short review.